Negative electrode binder, negative electrode sheet and secondary battery
By using a granular polymer with a specific particle size and composition as the negative electrode binder, the problem of low lithium ion transmission rate caused by styrene butadiene rubber is solved, the low-temperature discharge performance and lithium ion transmission ability of the battery are improved, and the adhesion between the negative electrode active substance and the current collector is enhanced.
Patent Information
- Application Number
- CN202411819435.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing styrene butadiene rubber is used as the negative electrode binder, and the lithium ion transmission rate is low, resulting in a reduced discharge rate performance of the battery in a low temperature environment.
Particular polymers are used as the negative electrode binder. The polymers include vinyl aromatic structural units and acrylate structural units. The particle size D10 is 200-1300nm, D50 is 400-1500nm, D90 is 500-2000nm, and the glass transition temperature Tg is -50~110℃. By adjusting the polymerization conditions, the particle size distribution and composition are controlled to improve the lithium ion transport capacity.
It improves the low-temperature performance of the battery, improves the transmission rate of lithium ions, reduces the internal resistance of the battery, enhances the adhesion between the negative electrode active substance and the current collector, and improves the low-temperature discharge rate performance of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a negative electrode binder, a negative electrode sheet and a secondary battery. Background Art
[0002] A lithium-ion battery comprises a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises a negative electrode active material layer, which is formed by coating a negative electrode slurry on at least one side of a negative electrode current collector and drying the negative electrode slurry, wherein the negative electrode slurry comprises a negative electrode binder, a negative electrode active material and a conductive agent, wherein the negative electrode binder is a polymer compound that adheres the negative electrode active material and the conductive agent to the negative electrode current collector, and has the function of enhancing the contact between the negative electrode active material, the conductive agent and the negative electrode current collector and stabilizing the electrode sheet structure.
[0003] In the existing negative electrode slurry formula, styrene butadiene rubber is used as the negative electrode binder. Although styrene butadiene rubber has good bonding properties, the battery prepared using this binder has a low lithium ion transmission rate in a low temperature environment, which reduces the low temperature discharge rate performance of the battery. Summary of the invention
[0004] The technical problem to be solved by the present invention is that the existing styrene-butadiene rubber used as a negative electrode binder has a low lithium ion transmission rate, which reduces the low-temperature discharge rate performance of the battery. The invention provides a negative electrode binder, a negative electrode sheet and a secondary battery.
[0005] To solve the above technical problems, the present invention provides a negative electrode binder, including a granular polymer, wherein the polymer includes a vinylbenzene aromatic structural unit and an acrylate structural unit; the particle size D10 of the polymer is 200-1300nm, D50 is 400-1500nm, and D90 is 500-2000nm.
[0006] Preferably, the particle size distribution width of the polymer is less than 0.5.
[0007] Preferably, the glass transition temperature Tg of the polymer is -50~110°C.
[0008] Preferably, in the polymer, the mass ratio of the vinyl aromatic structural unit to the acrylic ester structural unit is (50-200):(100-300).
[0009] Preferably, in the polymer, the vinyl aromatic structural unit is selected from one or more of styrene monomer units, p-methylstyrene monomer units, p-ethylstyrene monomer units, m-methylstyrene monomer units, phenoxyethyl methacrylate monomer units, 2-butylene ethoxy phthalate monomer units, benzyl acrylate monomer units, 2-phenoxyethyl acrylate monomer units, biphenyl acrylate monomer units, phenoxydiethylene glycol acrylate monomer units, ethoxy polyethylene glycol o-phenylphenol acrylate monomer units, benzyl methacrylate monomer units, ethoxylated bisphenol A dimethacrylate monomer units, phenyl acrylate monomer units, and benzyl acrylate monomer units;
[0010] The acrylic acid ester structural unit is selected from butyl (meth)acrylate monomer unit, methoxydiethylene glycol methacrylate monomer unit, stearic methacrylate monomer unit, isooctadecyl methacrylate monomer unit, methyl (meth)acrylate monomer unit, isobutyl (meth)acrylate monomer unit, n-butyl (meth)acrylate monomer unit, tert-butyl (meth)acrylate monomer unit, cyclohexyl acrylate monomer unit, 2-methoxyethyl (methoxy)acrylate monomer unit, isopentyl (meth)acrylate monomer unit, pentyl (meth)acrylate monomer unit, octyl (meth)acrylate monomer unit, and methyl (meth)acrylate monomer unit. The monomer units include one or more of hexyl (meth)acrylate monomer units, dodecyl (meth)acrylate monomer units, propylene (meth)acrylate monomer units, isopropyl (meth)acrylate monomer units, isodecyl (meth)acrylate monomer units, butyl (meth)acrylate monomer units, hexadienyl (meth)acrylate monomer units, vinyl (meth)acrylate monomer units, cyclohexyl (meth)acrylate monomer units, lauryl (meth)acrylate monomer units, methylhexyl (meth)acrylate monomer units, propylenehexyl (meth)acrylate monomer units, and formyloxyethyl (meth)acrylate monomer units.
[0011] Preferably, the polymer further includes functional structural units, which include acrylamide monomer units, 2-(tetrahydro-2-furanyl) methyl acrylate monomer units, cyclotrimethylolpropane formal acrylate monomer units, 2-hydroxymethylpropyl acrylate monomer units, acrylonitrile monomer units, 4-hydroxybutyl acrylate monomer units, acrylamide acid monomer units, vinyltrimethoxysilane monomer units, vinyltriethoxysilane monomer units, vinyldimethoxysilane monomer units, vinylethoxysilane monomer units, methacryloxypropyltrimethoxysilane monomer units, vinyltriethoxysilane monomer units, allyltrimethoxysilane monomer units, methylallyltrimethoxysilane monomer units, hydroxyethyl acrylate monomer units, and hydroxypropyl acrylate monomer units.
[0012] Preferably, in the polymer, the mass ratio of the vinyl aromatic structural unit, the acrylate structural unit, and the functional structural unit is (50-200): (100-300): (10-50).
[0013] Preferably, the polymer further comprises an acrylic acid structural unit, and the acrylic acid structural unit is selected from one or more of a methacrylic acid monomer unit and an acrylic acid monomer unit; the mass ratio of the acrylate structural unit to the acrylic acid structural unit is (20-100): (0.1-50).
[0014] In a second aspect, the present application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode binder, and the negative electrode binder is the negative electrode binder as described above.
[0015] In a third aspect, the present application provides a secondary battery, comprising a positive electrode sheet, a separator and the negative electrode sheet as described above.
[0016] Compared with the prior art, the negative electrode binder provided by the present application includes a granular polymer, the polymer includes a vinyl aromatic structural unit and an acrylate structural unit, and the particle size D10 of the polymer is 200-1300nm, D50 is 400-1500nm, and D90 is 500-2000nm. After the negative electrode slurry containing the negative electrode binder with the above-mentioned particle size characteristics is made into a negative electrode sheet, the diffusion resistance between the electrodes is relatively small, and the diffusion rate of lithium ions between the electrode particles is faster, thereby improving the transmission capacity of lithium ions, improving the low temperature performance of the battery, and improving the low temperature discharge rate performance of the battery. At the same time, the negative electrode sheet prepared by the negative electrode binder provided by the present invention is conducive to reducing the internal resistance of the lithium ion battery and improving the low temperature performance of the battery. In addition, the negative electrode binder is in firm contact with the negative electrode active material, and the peeling force is significantly improved. DETAILED DESCRIPTION
[0017] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0018] On the one hand, an embodiment of the present application provides a negative electrode binder, including a granular polymer, wherein the polymer includes a vinylbenzene aromatic structural unit and an acrylate structural unit; the particle size D10 of the polymer is 200-1300nm, D50 is 400-1500nm, and D90 is 500-2000nm.
[0019] Preferably, the D10 of the polymer is 300-1200 nm, more preferably 500-800 nm. Specifically, the D10 of the polymer can be 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm, 1000 nm, 1050 nm, 1100 nm, 1150 nm, 1200 nm, 1250 nm.
[0020] Preferably, the D50 of the polymer is 500-1400nm, more preferably 600-1000nm. Specifically, the D50 of the polymer can be 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1000nm, 1050nm, 1100nm, 1150nm, 1200nm, 1250nm, 1300nm, 1350nm, 1400nm, 1450nm.
[0021] Preferably, the D90 of the polymer is 800-1800nm, more preferably 1000-1500nm. Specifically, the D90 of the polymer can be 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1000nm, 1050nm, 1100nm, 1150nm, 1200nm, 1250nm, 1300nm, 1350nm, 1400nm, 1450nm, 1500nm, 1550nm, 1600nm, 1650nm, 1700nm, 1750nm, 1800nm, 1850nm, 1900nm, 1950nm.
[0022] Preferably, the particle size distribution width of the polymer is less than 0.5, more preferably 0.0001-0.5, and further preferably 0.05-0.4. As is well known in the prior art, the particle size distribution width is calculated by (D90-D10) / D50 of the particles.
[0023] In the present invention, when the particle size of the polymer is within the range disclosed in this application and the particle size distribution width of the polymer is below 0.5, it is very beneficial to further improve the lithium ion transmission capacity, improve the low temperature performance of the battery, and improve the low temperature discharge rate performance of the battery.
[0024] As is known in the prior art, the particle size and particle size distribution width of the particles obtained after polymerization can be adjusted by adjusting the composition of the polymerization reaction monomers, the mixing speed of the monomers and the initiator, and the stirring speed during the reaction.
[0025] Preferably, the glass transition temperature Tg of the polymer is -50 to 110° C. More preferably, it is -30 to 80° C. In the present invention, when the glass transition temperature Tg of the polymer is -50 to 110° C., it is very beneficial to improve the peeling force of the negative electrode sheet when good contact between the polymer particles and the negative electrode active material and the conductive agent is achieved.
[0026] In the present invention, preferably, in the polymer, the mass ratio of the vinyl aromatic structural unit to the acrylic ester structural unit is (50-200): (100-300).
[0027] According to the present invention, the above-mentioned vinyl aromatic structural unit refers to the corresponding structural unit existing in the polymer after the vinyl aromatic monomer is polymerized. Similarly, the acrylate structural unit refers to the corresponding structural unit existing in the polymer after the acrylate monomer is polymerized. Similarly, the mass ratio of the vinyl aromatic structural unit to the acrylate structural unit can be based on the mass ratio of the vinyl aromatic monomer raw material to the acrylate monomer raw material when preparing the polymer.
[0028] Preferably, in the polymer, the vinyl aromatic structural unit is selected from one or more of a styrene monomer unit, a p-methylstyrene monomer unit, a p-ethylstyrene monomer unit, a m-methylstyrene monomer unit, a phenoxyethyl methacrylate monomer unit, a 2-butylene ethoxy phthalate monomer unit, a benzyl acrylate monomer unit, a 2-phenoxyethyl acrylate monomer unit, a biphenyl acrylate monomer unit, a phenoxydiethylene glycol acrylate monomer unit, an ethoxylated polyethylene glycol o-phenylphenol acrylate monomer unit, a benzyl methacrylate monomer unit, an ethoxylated bisphenol A dimethacrylate monomer unit, a phenyl acrylate monomer unit, and a benzyl acrylate monomer unit.
[0029] The vinyl aromatic structural units contained in the polymer can improve the thermal stability, chemical stability, mechanical properties and electrical conductivity of the negative electrode binder.
[0030] Preferably, the acrylic acid ester structural unit is selected from butyl (meth)acrylate monomer unit, methoxydiethylene glycol methacrylate monomer unit, stearic methacrylate monomer unit, isooctadecyl methacrylate monomer unit, methyl (meth)acrylate monomer unit, isobutyl (meth)acrylate monomer unit, n-butyl (meth)acrylate monomer unit, tert-butyl (meth)acrylate monomer unit, cyclohexyl acrylate monomer unit, 2-methoxyethyl acrylate monomer unit, isopentyl (meth)acrylate monomer unit, pentyl (meth)acrylate monomer unit, octyl (meth)acrylate monomer unit, One or more of the following monomer units: hexyl (meth)acrylate monomer unit, dodecyl (meth)acrylate monomer unit, propylene (meth)acrylate monomer unit, isopropyl (meth)acrylate monomer unit, isodecyl (meth)acrylate monomer unit, butyl (meth)acrylate monomer unit, hexadienyl (meth)acrylate monomer unit, vinyl (meth)acrylate monomer unit, cyclohexyl (meth)acrylate monomer unit, lauryl (meth)acrylate monomer unit, methylhexyl (meth)acrylate monomer unit, propylenehexyl (meth)acrylate monomer unit, and formyloxyethyl (meth)acrylate monomer unit.
[0031] The above-mentioned acrylate structural units contained in the polymer help the binder to adapt to the volume changes of the negative electrode material during the battery charging and discharging process, and reduce the generation of stress and cracks; the addition of acrylate monomers helps to improve the bonding performance, mechanical properties, chemical stability and thermal stability of the negative electrode binder. The acrylate monomers are conductive, which improves the ionic conductivity of the negative electrode binder, helps to increase the lithium ion transmission rate of the electrode, and improves the low-temperature discharge performance of the battery.
[0032] According to the present invention, preferably, the polymer further comprises a functional structural unit. The functional structural unit refers to a corresponding structural unit existing in the polymer after the functional monomer is polymerized.
[0033] The functional structural units include one or more of acrylamide monomer units, 2-(tetrahydro-2-furanyl) methyl acrylate monomer units, cyclotrimethylolpropane formal acrylate monomer units, 2-hydroxymethylpropyl acrylate monomer units, acrylonitrile monomer units, 4-hydroxybutyl acrylate monomer units, acrylamide acid monomer units, vinyltrimethoxysilane monomer units, vinyltriethoxysilane monomer units, vinyldimethoxysilane monomer units, vinylethoxysilane monomer units, methacryloxypropyltrimethoxysilane monomer units, vinyltriethoxysilane monomer units, allyltrimethoxysilane monomer units, methylallyltrimethoxysilane monomer units, hydroxyethyl acrylate monomer units, and hydroxypropyl acrylate monomer units.
[0034] When the polymer contains the aforementioned vinyl aromatic structural units and acrylate structural units, the functional structural units can cooperate with the vinylbenzene structural units and the acrylate structural units to improve the bonding performance, enhance the adhesion between the binder and the electrode material and the current collector, form a three-dimensional network structure, improve the cohesion and mechanical strength of the binder, improve the compatibility of the binder with the negative electrode active material, and improve the flexibility and thermal stability of the binder.
[0035] Preferably, in the polymer, the mass ratio of the vinyl aromatic structural unit, the acrylate structural unit, and the functional structural unit is (50-200): (100-300): (10-50). In this case, it is helpful to form negative electrode binder particles with large particle size, which have good thermal stability, chemical stability, mechanical properties, flexibility and conductivity, strong adhesion, and large particle size negative electrode binder, which helps to improve the transmission rate of lithium ions, reduce the internal resistance of the battery, and improve the low temperature discharge rate performance of the battery.
[0036] Preferably, the polymer further comprises acrylic structural units.
[0037] Similarly, the acrylic structural unit refers to the corresponding structural unit present in the polymer after the acrylic monomer is polymerized. The acrylic structural unit is selected from one or more of methacrylic acid monomer units and acrylic acid monomer units. When the polymer contains the above acrylic structural unit, it helps to improve the dispersibility of the negative electrode binder and the negative electrode active material, and improve the bonding, flexibility, mechanical properties, conductivity and water resistance of the negative electrode binder.
[0038] In a further preferred case, the mass ratio of the acrylate structural unit to the acrylic acid structural unit is (20-100): (0.1-50). If the mass ratio of the acrylate structural unit to the acrylic acid structural unit is too low, too little acrylate monomer is added, and the prepared binder has reduced flexibility, reduced bonding performance, and reduced conductivity. If the mass ratio of the acrylate structural unit to the acrylic acid structural unit is too high, too little acrylic monomer is added, and the dispersion performance of the negative electrode binder and the negative electrode active material is reduced.
[0039] In some embodiments, the negative electrode binder further comprises a surfactant. The mass ratio of the vinyl aromatic structural unit, the acrylate structural unit, the functional structural unit and the surfactant is (50-200): (100-300): (10-50): (0.1-5).
[0040] Specifically, the added surfactant forms a hydration wall on the surface of small-sized polymer particles (or small-sized latex particles) through hydration to prevent the latex particles from agglomerating, thereby forming a stable emulsion. The mass ratio of the vinyl aromatic structural unit, the acrylate structural unit, the functional structural unit and the non-ionic surfactant is in the range of (50-200): (100-300): (10-50): (0.1-5), which helps the ionic surfactant to be adsorbed on the polymer surface, prevents the polymer particles from agglomerating and merging, and forms the large-sized polymer provided by the present invention.
[0041] In some embodiments, the surfactant is selected from one or more of sodium dodecylbenzene sulfonate, ammonium nonylphenol polyoxyethylene ether sulfate, sodium dodecyl sulfate, sodium octanoate, sodium octyl sulfonate, sodium stearate, sodium octyl sulfate, sodium polyethoxyoctyl ether sulfate, sodium polyethylene ether phytate, polyethoxyoctanol ether, phosphate ester, octylphenol polyoxyethylene ether, polyethoxyoctanol, polyethylene glycol octyl ether, octanol polyoxyethylene ether, polyethylene ether phytate, octylphenol ethoxylate, phytate, polyethylene ether octyl ether, dodecyl polyoxyethylene ether, and polyvinyl octanoate.
[0042] The negative electrode binder provided in the present application can be prepared based on the aforementioned raw material monomers provided in the present application by a method commonly used in the field of chemical synthesis. For example, the preparation method may include the following steps: preparing a pre-emulsion: uniformly mixing vinyl aromatic monomers, acrylate monomers, selectively added functional monomers, and selectively added acrylic monomers with a solvent and a surfactant, and heating (60-90°C) and stirring at a stirring speed of 100-1500rpm, adding an initiator to carry out a polymerization reaction, and obtaining the negative electrode binder after the reaction is completed.
[0043] The amounts of vinyl aromatic monomers, acrylic ester monomers, optionally added functional monomers, and optionally added acrylic monomers are as described above.
[0044] The initiator includes one or more of benzoyl peroxide, lauroyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, diisopropyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate), methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, potassium persulfate, sodium persulfate, ammonium persulfate, azobisisobutyronitrile, and azobisisoheptylonitrile. Those skilled in the art can adjust the amount of the initiator added according to actual use needs, for example, the amount of the initiator added can be 0.1-2% relative to the total amount of the monomer mixture.
[0045] In some embodiments, the solvent may be deionized water. The amount of the solvent used may be adjusted by those skilled in the art according to actual use requirements. For example, the amount of the solvent used may be 50-500% relative to the total amount of the monomer mixture.
[0046] In a second aspect, the present application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode binder, and the negative electrode binder is the negative electrode binder as described above.
[0047] In some embodiments, the negative electrode current collector includes copper foil, nickel foil, composite copper foil, carbon-coated copper foil, etc.
[0048] In some embodiments, the negative electrode active material layer further includes a negative electrode active material, a negative electrode conductive agent, and a thickener.
[0049] Negative electrode active materials include graphite, hard carbon, soft carbon, silicon-carbon negative electrode, silicon-based negative electrode, etc.
[0050] The negative electrode conductive agent includes one or more of graphite, acetylene black, conductive carbon black, graphene, carbon fiber, carbon nanotube and Ketjen black.
[0051] In a third aspect, the present application provides a secondary battery, comprising a positive electrode sheet, a separator and the negative electrode sheet as described above.
[0052] The present invention is further described below by way of examples.
[0053] The binder composition, negative electrode composition, negative electrode sheet and lithium ion battery disclosed in the present invention are specifically described.
[0054] Example 1
[0055] 1) Preparation of negative electrode binder
[0056] S1: Material preparation for pre-emulsion preparation:
[0057] 50 parts of styrene, 50 parts of p-methylstyrene, 50 parts of p-ethylstyrene; 100 parts of butyl acrylate, 20 parts of amyl acrylate, 50 parts of hexadienyl acrylate; 10 parts of acrylamide, 10 parts of acrylonitrile, 10 parts of vinyl dimethoxy silane, 2 parts of acrylic acid;
[0058] The surfactant is: 1 part of dodecyl polyoxyethylene ether and 1 part of sodium dodecyl sulfate;
[0059] Initiator: 2 parts of sodium persulfate;
[0060] Solvent: 500 parts of water.
[0061] S2: Preparing a pre-emulsion: uniformly mixing the above-mentioned vinyl aromatic monomers, acrylate monomers, functional monomers, acrylic monomers, surfactants and solvents to obtain a pre-emulsion.
[0062] S3: Initiator sodium persulfate and pre-emulsion are gradually added into the reaction container at the same time, and polymerization reaction is carried out under stirring condition of 300rpm. During the polymerization process, monomers are gradually polymerized into polymers. As the polymerization reaction proceeds, large-size latex particles are gradually formed. After the reaction is completed, a white emulsion is obtained, which is then dried to prepare a negative electrode binder.
[0063] Example 2
[0064] Most of the steps of this embodiment are the same as those of embodiment 1, except that in step S1, the types and weight portions of the vinyl aromatic monomers are different, specifically as follows: 50 parts of m-methylstyrene.
[0065] Example 3
[0066] Most of the steps of this embodiment are the same as those of embodiment 1, except that in step S1, the types and weight parts of the vinyl aromatic monomers are different, specifically as follows: 100 parts of styrene, 50 parts of p-methylstyrene, and 50 parts of p-ethylstyrene.
[0067] Example 4
[0068] Most of the steps of this embodiment are the same as those of embodiment 1, except that in step S1, the type and weight of the vinyl aromatic monomer are different, specifically as follows: 20 parts of styrene.
[0069] Example 5
[0070] Most of the steps of this embodiment are the same as those of embodiment 1, except that in step S1, the types and weight proportions of the vinyl aromatic monomers are different, specifically: 100 parts of styrene, 100 parts of p-methylstyrene, and 100 parts of p-ethylstyrene.
[0071] Example 6
[0072] Most of the steps of this embodiment are the same as those of embodiment 1, except that in step S1, the types and weights of functional monomers are different, specifically: 20 parts of methyl methacrylate, 20 parts of hydroxyethyl acrylate, and 10 parts of vinyl dimethoxy silane.
[0073] Example 7
[0074] Most of the steps of this embodiment are the same as those of embodiment 1, except that in step S1, the types and weight portions of the functional monomers are different, specifically as follows: 5 parts of vinyl diethoxysilane.
[0075] Example 8
[0076] Most of the steps of this embodiment are the same as those of Embodiment 1, except that in step S1, the types and weights of functional monomers are different, specifically: 20 parts of acrylamide acid, 20 parts of hydroxyethyl acrylate, 10 parts of vinyl dimethoxy silane, and 20 parts of vinyl triethoxy silane.
[0077] Comparative Example 1
[0078] Most of the steps of this comparative example are the same as those of Example 1, except that in step S1, no functional monomer is added and the stirring speed is adjusted. The rest is the same as Example 1.
[0079] Comparative Example 2
[0080] Most of the steps of this comparative example are the same as those of Example 1, except that in step S1, no vinylbenzene monomer is added, and the stirring speed is adjusted. The rest is the same as Example 1.
[0081] Comparative Example 3
[0082] Most of the steps of this comparative example are the same as those of Example 1, except that in step S1, no acrylic acid ester monomer is added, and the stirring speed is adjusted. The rest is the same as Example 1.
[0083] Performance Test:
[0084] The negative electrode binders prepared in the above-mentioned embodiments and comparative examples were used to prepare negative electrode sheets and lithium-ion batteries according to the prior art, and the following tests were performed. The negative electrode sheet's negative electrode active material was graphite, the negative electrode conductive agent was conductive carbon black, and the thickener was CMC. The mass ratio of the graphite, conductive carbon black, thickener, and binder composition was 96.8:1.0:1.2:1.0
[0085] 1) The particle size of the negative electrode binder was tested using a particle size analyzer. The test results are shown in Table 1.
[0086] 2) Negative electrode peel strength test:
[0087] After the negative electrode sheet prepared above was compacted, the peel strength of the negative electrode sheet was measured using a tensile testing machine, and the test method was based on GB2792-2014.
[0088] 3) Rate performance test:
[0089] The batteries prepared in the above-mentioned embodiments and comparative examples were charged at a constant current of 1C to a voltage of 4.3V, and then charged at a constant voltage to a cut-off current of 0.05C. The fully charged batteries were discharged at 1C, and the discharge capacity C1 of the batteries was recorded. Then the cycle was repeated once more, with a constant current of 1C charged to a voltage of 4.3V, and then charged at a constant voltage to a cut-off current of 0.05C. The batteries were placed in a -10°C freezer, and discharged at a constant current of 1C and 2C to 2.75V, respectively, and the discharge capacity C2 of the batteries was recorded. At this time, the ratio of the discharge capacity at -10°C to the charge capacity at 0.5C at room temperature is the low-temperature capacity retention rate of the battery; low-temperature discharge capacity retention rate = C2 / C1*100%.
[0090] The test results of 1)~3) are shown in Table 1.
[0091] Table 1
[0092]
[0093] It can be seen from Table 1 that the negative electrode binder provided by the present invention has excellent peel strength and can effectively improve the low-temperature discharge rate performance of the battery.
[0094] By comparing the test results of Example 1 and Comparative Examples 1-3, it can be seen that when the particle size of the negative electrode binder is not within the range of the present invention, the peel strength of the binder is significantly reduced, and the low-temperature discharge rate performance of the battery is also reduced.
[0095] It can be seen from the test results of Comparative Examples 1 and 7 that when the mass ratio of the acrylate structural unit to the functional structural unit is not within the preferred range of the present invention, the peel strength of the adhesive is significantly reduced, and the low-temperature discharge rate performance of the battery is also reduced.
[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A negative electrode binder, characterized in that: A particulate polymer comprising vinyl aromatic structural units, acrylic structural units, functional structural units and acrylate structural units; The particle size D10 of the polymer is 200-1300nm, D50 is 400-1500nm, and D90 is 500-2000nm; The functional structural units include one or more of acrylamide monomer units, 2-hydroxymethylpropyl acrylate monomer units, acrylonitrile monomer units, 4-hydroxybutyl acrylate monomer units, vinyltrimethoxysilane monomer units, vinyltriethoxysilane monomer units, vinyldimethoxysilane monomer units, vinylethoxysilane monomer units, methacryloxypropyltrimethoxysilane monomer units, allyltrimethoxysilane monomer units, methylallyltrimethoxysilane monomer units, hydroxyethyl acrylate monomer units, and hydroxypropyl acrylate monomer units; The mass ratio of the acrylate structural unit to the acrylic structural unit is (20-100): (0.1-50); The mass ratio of the vinyl aromatic structural unit, the acrylate structural unit, and the functional structural unit is (50-200): (100-300): (10-50); In the polymer, the vinyl aromatic structural unit is selected from one or more of styrene monomer units, p-methylstyrene monomer units, p-ethylstyrene monomer units, and m-methylstyrene monomer units; The acrylic acid ester structural unit is selected from one or more of butyl (meth)acrylate monomer units, stearic methacrylate monomer units, isostearyl methacrylate monomer units, methyl (meth)acrylate monomer units, cyclohexyl acrylate monomer units, pentyl (meth)acrylate monomer units, octyl (meth)acrylate monomer units, hexyl (meth)acrylate monomer units, dodecyl (meth)acrylate monomer units, propylene (meth)acrylate monomer units, isopropyl (meth)acrylate monomer units, isodecyl (meth)acrylate monomer units, butyl (meth)acrylate monomer units, hexadienyl (meth)acrylate monomer units, vinyl (meth)acrylate monomer units, methylcyclohexyl acrylate monomer units, methylhexyl (meth)acrylate monomer units, and propylene hexyl (meth)acrylate monomer units.
2. The negative electrode binder according to claim 1, characterized in that The particle size distribution width of the polymer is less than 0.
5.
3. The negative electrode binder according to claim 1, characterized in that The glass transition temperature Tg of the polymer is -50 to 110°C.
4. The negative electrode binder according to any one of claims 1 to 3, characterized in that: In the polymer, the mass ratio of the vinyl aromatic structural unit to the acrylic ester structural unit is (50-200):(100-300).
5. The negative electrode binder according to claim 1, characterized in that The acrylic structural unit is selected from one or more of methacrylic acid monomer units and acrylic acid monomer units.
6. A negative electrode sheet, characterized in that: The invention comprises a negative electrode current collector and a negative electrode active material layer arranged on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode binder, and the negative electrode binder is the negative electrode binder according to any one of claims 1 to 5.
7. A secondary battery, characterized in that: It comprises a positive electrode sheet, a separator and the negative electrode sheet as claimed in claim 6.
Citation Information
Patent Citations
Aqueous pressure sensitive adhesive composition with multimodal particle size distribution
CN116601190A